2020
DOI: 10.1002/adsu.201900137
|View full text |Cite
|
Sign up to set email alerts
|

Approaching High‐Performance Supercapacitors via Enhancing Pseudocapacitive Nickel Oxide‐Based Materials

Abstract: Nickel oxide, as a typical pseudocapacitive material, holds great promise for boosting the energy storage capability of supercapacitors (SCs) owing to its great advantages, such as high theoretical capacitance value, low‐cost, good stability, and environmentally benign nature. Nevertheless, many obstacles, including low intrinsic conductivity and limited surfice electrochemically active sites, need to be overcome before its practical implementation. In this review, the recent advances on nickel oxide‐based ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 164 publications
(147 reference statements)
0
16
0
Order By: Relevance
“…Fig. 3a displays the CV curves of the Ni@NiO-35 A electrode at different scan rates, revealing the electrochemical redox properties of the 3D nano-folded Ni@NiO with a pair of redox peaks at the potential of 0–0.5 V. Specifically, a pair of redox peaks can be observed at the potential locations of 0.35 V and 0.17 V, which are mainly from the reversible redox reaction of NiO as follows: 29,30 NiO + OH − ↔ NiOOH + e − …”
Section: Resultsmentioning
confidence: 99%
“…Fig. 3a displays the CV curves of the Ni@NiO-35 A electrode at different scan rates, revealing the electrochemical redox properties of the 3D nano-folded Ni@NiO with a pair of redox peaks at the potential of 0–0.5 V. Specifically, a pair of redox peaks can be observed at the potential locations of 0.35 V and 0.17 V, which are mainly from the reversible redox reaction of NiO as follows: 29,30 NiO + OH − ↔ NiOOH + e − …”
Section: Resultsmentioning
confidence: 99%
“…Notably, the SC market remains on a rising path, with an anticipated value of USD 450 million in 2019 and a compound annual growth rate of 14.1% during the forecast period (2019–2024). [ 130 ] In ref. [131], they demonstrated in situ conversion of commercial polyimide (PI) films into porous graphene through laser direct writing for the fabrication of flexible supercapacitors with enhanced capacitive performance.…”
Section: Energy Storage Systemsmentioning
confidence: 99%
“…Despite making considerable progress, the low decomposition voltage of water (1.23 V) leads to a poor energy density of SCs (Yi et al, 2020). It is also reported that the cycle performance of SCs will deteriorate after adding redox additives to the aqueous electrolytes (Chodankar et al, 2016;Singh and Chandra, 2016).…”
Section: Redox Mediated Aqueous Electrolytesmentioning
confidence: 99%
“…Supercapacitors (SCs) are a new type of energy storage equipment filling the gap between secondary batteries and traditional capacitors (Hui et al, 2019;Poonam et al, 2019;Zhi-yu et al, 2019;Alipoori et al, 2020;Cheng et al, 2020;Iqbal et al, 2020;Li and Liang, 2020;Mohd Abdah et al, 2020;Panda et al, 2020;Yi et al, 2020). SCs are believed to be one of the most promising candidates due to their fast charging/discharging capability, long cycle life, high power density, and high safety (Zhang W. et al, 2017;Zhang et al, 2018;Afif et al, 2019).…”
Section: Introductionmentioning
confidence: 99%